Pengaruh Posisi Merangkak Terhadap Kemajuan Persalinan Kala I Fase Aktif Pada Primigravida Di BPS Ny.Endang Sumaningdyah Kota Kediri - Rahajeng Siti Nur Rahmawati; Ira Titisari; Susanti Pratamaningtyas (coba, 2014)
The research were reported that 15,4% woman which in complication in labour, where the complication active phase length is mostly experienced by primigravida. On course hand knee position estimated can assist to turn around fetus, shortening conjugata vera and improve room of flank so that good for quicken progress of labour. Intention of this research is to know effect of hand knee position to quicken progress of I active phase at primigravida at BPS.Endang Sumaningdyah Kediri. Research desaign used correlation. Selected by Sampel is mother of primigravida in I active phase at BPS.Endang Sumaningdyah Kediri. Technique sampling used total sampling. Amount of sampel criteria is counted 10 responded. Technique data collecting responded using observation sheet and partograf which filled by researcher. Analysis data used Fhiser Exact’s Test with level of significant 5%. Result of which is got P ( 0,033 ) <  ( 0,05) so that can be conclusion that there is effect of hand knee position to quicken progress I active phase at primigravida at BPS Endang Sumaningdyah Kediri. Suggestion for next research to be more comprehend about factors director to progress of labour and to research place to be can continue the habitual in suggesting mother to use hand knee position to quicken labour process. Key word: hand knee position , quicken progress of labour, first active phase